Exploring The Role Of Exploratory Testing In Agile Software Development Environments - Majid Ali; Nabeel Ali Khan; Mudasira Sarfraz; Sehrish Riaz; Tahir Mehmood; Shamila Ghafoor (Spectrum of Engineering Sciences, 2025)
Agile software development environments are characterizedbytheir focus on exploratory testing as a principal methodology. The system's adaptation to requirements allows roomfor creativity in the treatment of areas that have so far not been takenupbyformal tests only. In this way, the central question the study answers is How can I use and are these tests the right ones to implement regarding the context of agility? through a systematic review of the literature (SLR) which will be based on collecting the entire world-released research papers up to the current date. We expect to identify what is already known about these topics, different ways of their implementation, whether such activities are associated with any benefits, and what the problems are with them. To this end, various scholarly databases like IEEE Xplore, ACM digital library, Springer Link in addition to others or even peer reviewed sources have been explored. However, only those journal articles which meet the eligibility criteria set by the authors, i.e., they have the content capable of addressing the issues relatedtothe topic under investigation, were considered valid materials for use in this study. These relevant papers were selected while their relevant ones or those that had insufficient validity were excluded. As a result, the total number of papers gathered was seventeen after a project whose primary purpose was to verify the selection standards were met ’s end. However, it was noted fromour analysis that lack management backing might be because few people know much about its advantages or face difficulties related with documentation being obsolete hence there is need for more empirical research if successful integration into scrum process framework stills remains a goal. This article summarizes agilesoftware testing knowledge through a systematic review. Information has been gathered from various sources inorder togive fact based insights. These findings serve as a necessity for people doing exploratory testing as they will have to come up with new hypothesis or ideas while those that align test processes with expected project results after implementation get a chancefortheir wishes about working software to come true. Keywords: Exploratory testing, Agile software development, Quality assurance, Software development methodologies